Consumer Buying Interest In Old Coffee's Marketing Strategy - Fitri Devi Lestari Izaak; Rini Hadiyanti (International Forum of Researchers and Lecturers, 2022)
The goal is to get a sense of the shop ambiance, promotions, and customer purchasing interest at Kopitema. The study technique employed is a descriptive and verification strategy. The procedure of gathering data by delivering questionnaires to Old Coffee customers as responses. Even while respondents' answers to promos are fairly positive, there are still low ratings, indicating that they still need to be improved. Similarly, consumer purchasing interest in Old Coffee based on respondents' comments is deemed strong, but the evaluation remains low and has to be improved. Partially, it was discovered that the shop environment impacts customer purchasing interest.